The establishment of the general microexpression recognition ability and its relevant brain activity - Zhang, Jianxin; Yin, Ming; Shu, Deming; Liu, Dianzhi (Frontiers in Human Neuroscience, 2022)
The PREMERT by Zhang, Yin, Shu, & Liu (2020) could test the individual’s microexpression recognition ability with six microexpression Ms and six microexpression SDs, but it and other studies did not explore the general microexpression recognition ability (the GMERA), or could not test the GMERA effectively. Therefore, the current study put forward and established the GMERA with the behavioral data of Zhang, Yin, Shu, & Liu (2020) and explored the relevant resting state brain activity of the GMERA indicators to prove that the GMERA is an individual cognitive characteristic from brain mechanisms with the neuroimaging data of Zhang, Yin, Shu, & Liu (2020). The results showed: (1) There was a three-layer hierarchical structure in human microexpression recognition ability: the GMERA (the highest layer); recognition of a type of microexpression under different expression backgrounds (the second layer); recognition of a certain microexpression under a certain expression background (the third layer). A common factor GMERA was extracted from the six microexpression types recognition in PREMERT. Four indicators of the GMERA were calculated from six microexpression Ms and six microexpression SDs, such as GMERAL (level of GMERA), GMERAF (fluctuation of GMERA), GMERAB (background effect of GMERA) and GMERABF (fluctuation of GMERAB), which had good parallel-forms reliability, calibration validity and ecological validity. The GMERA provided a concise and comprehensive overview of the individual’s microexpression recognition ability. The PREMERT was proved a good test to measure the GMERA. (2) ALFFs in both eyes-closed and eyes-opened resting-states and ALFFs-difference could predict the four indicators of the GMERA. The relevant resting state brain areas were some areas of the expression recognition network, the microexpression consciousness and attention network, and the motor network for the change from expression backgrounds to microexpression. (3) The relevant brain areas of the GMERA and of different types of microexpression recognition belonged to the three cognitive processes, but the relevant brain areas of the GMERA were the “higher-order” areas to be more concise and critical than those of different types of microexpression recognition.